Double-shell microcapsule, preparation method of double-shell microcapsule, cement and preparation method of cement

By using bicapsules in cement, combining hydrophobic capsule core, porous inorganic capsule shell and mechanical protection of organic capsule shell, the problem of thermal insulation and corrosion resistance of cement materials in high-temperature and high-pressure environments is solved, and efficient Heat insulation and corrosion resistance.

CN119461948AInactive Publication Date: 2025-02-18CHENGDU UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202510031008.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing cement materials cannot take into account both thermal insulation and corrosion resistance, especially in high temperature and high pressure and brine environments rich in CO2 and H2S, they are easily damaged by corrosive fluids.

Method used

Using bicapsule microcapsule technology, the capsule core is composed of hydrophobic substances, the inorganic capsule shell has a porous structure, and the organic capsule shell is used for mechanical protection. By adding these microcapsules to the cement, low thermal conductivity and hydrophobic microcapsules are formed to prevent the migration of solution ions in the porous structure of the cement.

Benefits of technology

While retaining porous insulation properties, it can improve the corrosion resistance of cement, reduce the possibility of cement structure being corroded, and enhance the compatibility of cement with other raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461948A_ABST
    Figure CN119461948A_ABST
Patent Text Reader

Abstract

The invention discloses a double-shell microcapsule and a preparation method thereof, and cement and a preparation method thereof, and relates to the field of cement materials and preparation methods thereof, the double-shell microcapsule comprises a capsule core, an inorganic capsule shell and an organic capsule shell, the capsule core is coated in the inorganic capsule shell, and the organic capsule shell is coated outside the inorganic capsule shell; the capsule core has hydrophobicity, the inorganic capsule shell comprises a porous structure, the capsule core comprises a hydrophobic substance, and the organic capsule shell is arranged to mechanically protect the inorganic capsule shell; the inorganic capsule shell can react with a formation medium, and the organic capsule shell can be dissolved in the formation medium. The capsule-core microcapsule disclosed by the invention is applied to cement preparation, and the prepared cement material has relatively strong thermal insulation and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of cement materials and preparation methods thereof, and in particular to a double-shell microcapsule and a preparation method thereof, and cement and a preparation method thereof. Background Art

[0002] As a clean and renewable energy with wide distribution, abundant reserves and stable energy supply, geothermal energy is expected to provide important support for promoting green and low-carbon development and promoting the transformation of energy structure. Drilling is the only means of deep geothermal energy development. Due to the existence of geothermal gradient, the high-temperature fluid at the bottom of the geothermal well always conducts reverse heat transfer to the formation during the ascent process, resulting in a decrease in the outlet temperature of the geothermal well, affecting the utilization efficiency of geothermal resources. In view of the fact that the proportion of cement ring in the radial heat transfer direction is higher than the thickness of the casing wall, thermal insulation cementing cement is proposed. For geothermal thermal insulation cementing, the commonly used means are composite low thermal conductivity materials, such as hollow glass microspheres, floating beads, expanded perlite, vermiculite, etc. By increasing the proportion of pores in the material, the low thermal conductivity of the gas is used to improve the thermal insulation performance of the material. Geothermal wells are often in a high-temperature, high-pressure and CO2- and H2S-rich salt water environment. Conventional cementing cement is already facing a complex corrosive environment, and the porous structure in the thermal insulation cement makes it more susceptible to damage by corrosive fluids.

[0003] At present, the existing cement anti-corrosion technologies in acidic oil and gas reservoir cementing mainly include: ① improving material density, ② reducing the calcium-silicon ratio of the system, and ③ mixing organic inert anti-corrosion materials (latex, epoxy resin). However, methods ① and ② have limited effects on reducing porosity and alkalinity, and method ③ is limited by the maximum dosage and the formation of water permeable channels during the film formation process of the polymer film, which makes its corrosion resistance unsatisfactory and cannot completely cover the surface of the cement stone. Therefore, none of them can effectively prevent the migration of harmful ions in the cement stone, especially in the porous thermal insulation cementing cement stone. Summary of the invention

[0004] The purpose of the present invention is to provide a double-shell microcapsule and a preparation method thereof and a cement and a preparation method thereof, so as to solve the problem that cement in the prior art cannot take into account both thermal insulation and corrosion resistance.

[0005] In order to solve the above problems, firstly, an embodiment of the present invention provides a double-shell microcapsule, comprising a capsule core, an inorganic capsule shell and an organic capsule shell, wherein the capsule core is coated in the inorganic capsule shell, and the organic capsule shell is coated outside the inorganic capsule shell; The inorganic capsule shell comprises a porous structure, the capsule core comprises a hydrophobic substance, and the organic capsule shell is configured to mechanically protect the inorganic capsule shell; The inorganic capsule shell can react with the formation medium, and the organic capsule shell can be dissolved in the formation medium.

[0006] Optionally, the capsule core includes at least one of dimethyl silicone oil, polymethyl hydrogen siloxane and normal isoparaffin, the inorganic capsule shell includes SiO2 aerogel material, and the organic capsule shell includes polyvinyl alcohol.

[0007] In the embodiment of the present invention, the organosilicon waterproofing agent is used as a waterproofing agent for cement-based materials. After contacting with the moisture in the matrix, it reacts to generate a hydrophobic silicone resin film, which can be tightly combined with the matrix to form a solid waterproof layer. Its waterproof performance is better than paraffin, because the waterproof performance of paraffin relies on its wrapping of cement particles, and its own hydrophobic property causes it to have poor bonding with the cement matrix and poor adhesion, resulting in its performance in preventing solution ion corrosion is inferior to that of the silane waterproofing agent.

[0008] Optionally, the mass ratio of the capsule core to the inorganic capsule shell is 70-85:100, the thermal conductivity of the capsule core is 0.07-0.20 W / (m•K), and the thermal conductivity of the inorganic capsule shell is 0.015-0.020 W / (m•K).

[0009] Secondly, the embodiment of the present invention also provides a method for preparing a double-shell microcapsule, comprising the following steps: S1: mixing the capsule core and the inorganic capsule shell and drying them to obtain a single-layer microcapsule; S2: performing hydrophilic modification on the single-layer microcapsules to obtain inorganic single-shell low thermal conductivity microcapsules with hydrophilic exterior and hydrophobic core; S3: encapsulating the organic capsule shell to obtain double-shell microcapsules.

[0010] Optionally, the hydrophilic modification process in S2 includes spraying a silane coupling agent hydrolyzed solution on the surface of the single-layer microcapsule, and the mass fraction of the silane coupling agent hydrolyzed solution is 25-30%.

[0011] Specifically, Fig.13As shown, the chemical formula of the silane coupling agent is YR-Si(OR)3. A silane coupling agent with a polar end group, such as KH550, is used. After the silane coupling agent is hydrolyzed, it forms a bond with the Si on the surface of the aerogel. The other end is a hydrophilic polar group, which can improve the hydrophobic properties of the aerogel. If the silane coupling agent hydrolysis solution is not sprayed, the hydrophobic properties of the aerogel surface are not improved, and the aerogel has poor compatibility with cement, which may lead to stratification. In this way, the incorporation of aerogel may slow down the cement hydration process, thereby affecting the cement strength. The R group on the surface of the silane coupling agent also has a certain adverse effect of delaying the cement hydration. After the outer layer is coated with the PVA film, on the one hand, the polyhydroxyl group of PVA has good compatibility with the cement material, which can further improve the hydrophilicity of the microcapsule surface to prevent it from affecting the cement strength. On the other hand, the aerogel shell itself is a porous structure that relies on its own adsorption to form microcapsules, but the encapsulation ability of the hydrophobic capsule core is insufficient. The PVA film can further enhance the encapsulation effect of the capsule shell on the hydrophobic capsule core.

[0012] Optionally, the encapsulation of the organic capsule shell in S3 comprises re-coating the modified single-layer microcapsule with a polyvinyl alcohol aqueous solution; The mass fraction of the polyvinyl alcohol aqueous solution is 1-3%, because the exterior of the single-layer microcapsule is hydrophilic, which can ensure the coverage of the polyvinyl alcohol film.

[0013] Furthermore, an embodiment of the present invention also provides a cement, comprising a corrosion-resistant cementitious material, a thermal insulation admixture, an organic inert antiseptic emulsion and the above-mentioned double-shell microcapsule, and the weight percentages are: 65.8%~78.4%, 11.76%~24.44%, 2%~6% and 3.76%~7.84% respectively.

[0014] Optionally, the corrosion-resistant cementitious material includes slag and fly ash, and the weight ratio of slag to fly ash is 3.5-4.5:1; The organic inert antiseptic emulsion includes styrene-butadiene latex or epoxy resin; Finally, the thermal insulation admixture includes at least one of vitrified microspheres, fly ash floating beads, hollow glass microspheres, and silica aerogel.

[0015] The present invention also provides a method for preparing cement, comprising the following steps: Mixing the alkali-activated solution with the corrosion-resistant gelling material to obtain a corrosion-resistant mixed slurry; The thermal insulation admixture, the organic inert anticorrosive emulsion and the double-shell microcapsules prepared by the above preparation method are added into the corrosion-resistant mixed slurry and stirred and mixed to obtain cement slurry.

[0016] Optionally, the alkali-activated solution includes sodium silicate and NaOH. In the configuration of the alkali-activated solution, NaOH is weighed according to the following formula: m(NaOH)=27.78 / x-10.7, where m is the mass of NaOH, x is the modulus of sodium silicate, and x= 1.3~1.5.

[0017] Compared with the prior art, the embodiments of the present invention have the following advantages and beneficial effects:

[0018] 1. The double-shell microcapsules provided by the embodiment of the present invention sequentially arrange an inorganic capsule shell and an organic capsule shell outside the capsule core, set the capsule core to be hydrophobic, set the inorganic capsule shell to be a porous structure, and set the organic capsule shell to mechanically protect the inorganic capsule shell. When the cement prepared by the double-shell microcapsules is immersed in the corrosive medium of high-temperature formation water, the organic capsule shell is continuously dissolved, the inorganic capsule shell participates in the corrosion reaction, and the hydrophobic capsule core inside is released and infiltrates the matrix, forming a hydrophobic interface inside the cement stone to effectively prevent the migration of solution ions in the porous structure of the thermal insulation cement. The double-shell microcapsules provided by the embodiment of the present invention are used to prepare cement, which can not only ensure the porous thermal insulation performance, but also release hydrophobic substances to prevent the corrosive medium from entering the porous cement structure, thereby reducing the possibility of the cement structure being corroded. The organic capsule shell can protect the inorganic capsule shell to prevent the possibility of rupture during the mechanical stirring process of the double-shell microcapsules mixed with other raw materials during the preparation of cement.

[0019] 2. The embodiment of the present invention uses polyvinyl alcohol as the organic capsule shell, which can not only prevent the inorganic capsule shell from breaking, but also dissolve quickly in the geological medium, so that the hydrophobic capsule core can be quickly released to protect the cement structure.

[0020] 3. The embodiment of the present invention uses SiO2 aerogel as an inorganic capsule shell, which has extremely low thermal conductivity and good compatibility with cement, and is a good choice for cement-based thermal insulation admixtures. The porous structure and hydrophobic properties of aerogel can be used to better wrap the hydrophobic capsule core material through its own adsorption, and both the inorganic capsule shell and the hydrophobic capsule core have thermal insulation properties, so low thermal conductivity hydrophobic microcapsules can be formed.

[0021] 4. In the process of preparing microcapsules, the hydrophobic aerogel is used as the capsule shell in the embodiment of the present invention to ensure its effective adsorption to the hydrophobic capsule core. Before mixing with cement, the surface is hydrophilic modified and polyvinyl alcohol is used to form the outermost capsule shell. The characteristics of the polyhydroxy structure in the polyvinyl alcohol molecular chain can be used to improve the adhesion between the microcapsules and the cementitious material, thereby ensuring the mechanical strength of the cement paste.

[0022] 5. The embodiment of the present invention does not use commercial cement materials, maximizes the use of solid waste materials, avoids greenhouse gas emissions in the production process of cement raw materials, and is beneficial to environmental protection. In addition, the corrosion-resistant cementitious material system has low alkalinity, high temperature resistance, and strong resistance to acidic medium corrosion. The micro-beads in the fly ash have a small thermal conductivity, which is conducive to improving the thermal insulation performance of the cementitious system matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings: Figure 1 The anti-corrosion mechanism diagram of the double-shell microcapsule provided in the embodiment of the present invention, wherein Figure 1 (a) is a schematic diagram of the corrosive ion invasion state. Figure 1 (b) is a schematic diagram of the formation water intrusion state after the invasion of corrosive ions; Figure 2 A process diagram of double-shell microcapsules provided by an embodiment of the present invention; Figure 3 A particle size distribution diagram of microcapsules provided in an embodiment of the present invention; Figure 4 is a SEM scan of an embodiment of the present invention, wherein Figure 4 (a) is a SEM scan of a single-layer unmodified microcapsule prepared in Example 1, and (b) is a SEM scan of a double-shell microcapsule prepared in Example 1. Figure 4 (c) is a SEM scan of the inorganic capsule shell prepared in Example 1. Figure 4 (d) is a SEM scan of the organic capsule shell prepared in Example 1; Figure 5 TEM image of the double-shell microcapsule in Example 1; Figure 6 It is the energy spectrum line diagram of the double-shell microcapsule in Example 1; Figure 7 is the element distribution diagram of the double-shell microcapsule in Example 1, wherein Figure 7 (a) is a local TEM image of the microcapsule. Figure 7 (b) is the distribution diagram of Si element. Figure 7 (c) is the distribution diagram of O element. Figure 7 (d) is the distribution diagram of C element; Figure 8 is the apparent morphology of the corrosion condition of the specimen, where Figure 8(a) is a schematic diagram of the cement material prepared in Example 1 before corrosion, Figure 8 (b) is a schematic diagram of the cement material prepared in Example 1 after corrosion, wherein Figure 8 (c) is a schematic diagram of the cement material prepared in Comparative Example 1 before corrosion, wherein Figure 8 (d) is a schematic diagram of the cement material prepared in Comparative Example 1 after corrosion; Fig. 9 This is a comparison chart of thermal conductivity of cement materials prepared in some embodiments and comparative examples of the present invention; Fig.10 A comparison chart of the compressive strength attenuation rate of cement materials prepared in some embodiments and comparative examples of the present invention; Fig.11 This is a comparison chart of thermal conductivity of cement materials prepared in other embodiments and comparative examples of the present invention; Fig.12 A comparison chart of the compressive strength attenuation rate of cement materials prepared in other embodiments and comparative examples of the present invention; Fig.13 Schematic diagram of the bonding principle of the silane coupling agent according to an embodiment of the present invention. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0025] Therefore, the detailed description of the embodiments of the present invention provided below is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In order to solve the problem that cement in the prior art cannot take into account both thermal insulation and corrosion resistance, the embodiments of the present invention not only need to ensure the outlet water temperature of the well, but also need to improve the durability of the well body structure. On the one hand, it is necessary to reduce the thermal conductivity of cement and reduce the reverse heat transfer to the formation during the rising process of the high-temperature fluid at the bottom of the well to ensure the energy extraction efficiency; on the other hand, it is necessary to reduce the degree of corrosion of the porous structure of the insulating cement stone by the acidic medium and multi-ion solution of the formation, so as to ensure the integrity of the cement ring and extend the service life of the geothermal well.

[0027] Therefore, an embodiment of the present invention provides a method for preparing cement, which includes a method for preparing double-shell microcapsules, specifically comprising the following steps: (1) Preparation of double-shell microcapsules Step 1: Screen the inorganic porous shell of SiO2 aerogel material, dry it at a constant temperature, preheat and vigorously stir the low thermal conductivity hydrophobic core material, mix the inorganic shell material into the core material in proportion, continue stirring, filter and dry to obtain a single-layer microcapsule.

[0028] Specifically, the hydrophobic core microcapsule is a clustered particle structure, including a hydrophobic core and an outer shell for wrapping. The low thermal conductivity hydrophobic core is a mixture of one or more of dimethyl silicone oil, polymethylhydrogensiloxane, and normal isoparaffin, and its thermal conductivity is 0.07~0.20W / (m•K); the inorganic shell of the hydrophobic core microcapsule is composed of SiO2 aerogel, and its thermal conductivity is 0.015~0.020W / (m•K); the mass ratio of the core of the microcapsule to the inorganic shell is 70~85:100; preferably, the particle sizes D(0.1), D(0.5), and D(0.9) of the microcapsule are 103.41 μm, 360.08 μm, and 590.96 μm, respectively; illustratively, after the inorganic shell passes through a 50-mesh sieve, it is placed in a drying oven and dried at a constant temperature of 105°C for 8 h; the preheat treatment of the core material refers to placing the core material in a 60°C environment and heating it at a constant temperature for 2 h; the stirring process can use a strong stirrer, illustratively, setting the speed to 1000r / min and the stirring time to 5min; the continuous stirring process can be to adjust the stirring speed to 500r / min and continue stirring for 3min after the core and the inorganic shell are evenly mixed; the drying process can refer to filtering the mixed material, cooling it to room temperature and drying it for 24h.

[0029] Step 2: hydrophilic modification of low thermal conductivity hydrophobic capsule core microcapsules and organic capsule shell encapsulation, including preparing a silane coupling agent hydrolyzate solution, cooling to room temperature, spraying the silane coupling agent hydrolyzate solution on the surface of the microcapsules, stirring continuously during the process, static sealing, and after the heating process, obtaining low thermal conductivity microcapsules with hydrophilic exterior and hydrophobic capsule core; and then using a polymer aqueous solution to coat the low thermal conductivity microcapsules again to form organic / inorganic double-shell low thermal conductivity hydrophobic capsule core microcapsules.

[0030] Specifically, the silane coupling agent in the silane coupling agent hydrolysis solution is γ-aminopropyltriethoxysilane, and the mass fraction of the silane coupling agent is 25-30%; illustratively, the preparation process of the silane coupling agent hydrolysis solution is: after mixing the silane coupling agent with water, place it on a 60°C constant temperature magnetic stirrer, stir at a speed of 1000r / min for 5 minutes, and then cool to room temperature; the microcapsules sprayed with the silane coupling agent hydrolysis solution are statically sealed for 24 hours, and then dried at a constant temperature of 120°C for 15 minutes; the polymer in the polymer aqueous solution can be polyvinyl alcohol, and the concentration of the aqueous solution is 1-3%; the second coating process is to use the polymer aqueous solution to spray the surface of the SiO2 aerogel single-layer capsule shell hydrophobic capsule core microcapsule, and after spraying, dry it at a constant temperature of 60°C for 12 hours to form a second layer of organic polymer capsule shell.

[0031] (2) Preparation of cement The dry material of corrosion-resistant cementitious material is put into the container of cement slurry mixer, dried and stirred until uniform, an alkali-activated solution is prepared and poured into the dry material, and water is added in proportion to obtain corrosion-resistant cementitious slurry; the prepared low thermal conductivity microcapsules of double-shell hydrophobic capsule core, external thermal insulation admixture, and organic inert antiseptic emulsion are added to the corrosion-resistant cementitious slurry, fully stirred, and after curing, cement based on double-shell low thermal conductivity hydrophobic capsule core microcapsules is formed, wherein the thermal insulation admixture includes at least one of vitrified microspheres, fly ash floating beads, hollow glass microspheres, and silica aerogel.

[0032] Specifically, the weight percentages of the corrosion-resistant cementitious material, the thermal insulation admixture, the organic inert anticorrosive emulsion and the double-shell microcapsule are 65.8% to 78.4%, 11.76% to 24.44%, 2% to 6% and 3.76% to 7.84%, respectively. The dry material of the corrosion-resistant cementitious material includes slag: fly ash in a mass ratio of 3.5 to 4.5:1; illustratively, the dry material of the corrosion-resistant cementitious material can be added to the cement slurry mixer container and stirred at a low speed of 100 r / min for 2 minutes. Ensure sufficient mixing, and prepare the alkaline excitation solution by weighing 100 mL of liquid sodium silicate with a mass fraction of 24.8% and a modulus of 3.3, and weighing NaOH according to the following formula: m(NaOH)=27.78 / x-10.7, wherein m is the mass of NaOH, and x is the modulus of sodium silicate. In the embodiment of the present invention, the modulus of sodium silicate used is 1.3-1.5, and the organic inert anticorrosive emulsion is styrene-butadiene latex or epoxy resin; the mass ratio of water to corrosion-resistant gelling dry material is 0.4-0.6:1; illustratively, stirring can be performed at a low speed of 100 r / min for 5 min.

[0033] The double-shell low thermal conductivity hydrophobic capsule core microcapsules prepared in the embodiment of the present invention are as follows: Figure 1As shown in the figure, when the corrosive medium in the high-temperature formation water invades the cement, the organic capsule of polyvinyl alcohol is continuously dissolved, and the inorganic capsule participates in the corrosion reaction, and the hydrophobic capsule core inside is released, infiltrates the matrix, and forms silanol with active hydroxyl groups after contacting with CO2. The silanol reacts and condenses with the siloxy groups in the cement matrix to form a hydrophobic siloxane film. A hydrophobic interface is formed inside the cement stone to effectively prevent the migration of solution ions in the porous structure of the thermal insulation cement.

[0034] In order to better demonstrate the effect of the embodiment of the present invention, an experimental verification will be carried out below.

[0035] Embodiment 1: Provide a method for preparing cement, comprising the following steps: Preparation of low thermal conductivity hydrophobic capsule core microcapsules, the preparation process is referred to the attached Figure 2 As shown: (1) After passing the hydrophobic SiO2 aerogel through a 50-mesh sieve, it was placed in a drying oven and dried at a constant temperature of 105°C for 8 hours; (2) Preheating the capsule core material dimethyl silicone oil at 60°C for 2 hours; (3) Using a powerful stirrer, set the speed of dimethyl silicone oil to 1000 r / min, stir for 5 minutes, then pour in the hydrophobic SiO2 aerogel. After mixing evenly, adjust the stirring speed to 500 r / min and continue stirring for 3 minutes. The mass ratio of dimethyl silicone oil to hydrophobic SiO2 aerogel is 80:100. (4) After filtering the mixed material, cool it to room temperature and dry it for 24 hours to obtain surface hydrophobic single capsule shell low thermal conductivity microcapsules. The particle size distribution of surface hydrophobic single capsule shell low thermal conductivity microcapsules is as follows: Figure 3 As shown; Hydrophilic modification of low thermal conductivity hydrophobic core microcapsules and organic shell encapsulation: (5) Mixing γ-aminopropyltriethoxysilane and water in a ratio of 27:73, placing the mixture on a 60°C constant temperature magnetic stirrer, stirring at a speed of 1000 r / min for 5 min, and cooling the mixture to room temperature to prepare a silane coupling agent hydrolyzed solution; (6) Spray the hydrolyzed solution of silane coupling agent onto the surface of the microcapsules, stirring continuously during the spraying process to ensure uniformity; (7) The microcapsules sprayed with the hydrolyzed silane coupling agent solution in step (6) are statically sealed for 24 hours, and then heated at a constant temperature of 120° C. for 15 minutes to obtain inorganic single-shell low thermal conductivity microcapsules with a hydrophilic exterior and a hydrophobic core; (8) preparing a polyvinyl alcohol solution with a mass fraction of 3%, spraying the surface of SiO2 aerogel single-layer shell hydrophobic core microcapsules with the solution, and then drying at a constant temperature of 60°C for 12 hours to form organic / inorganic double-shell low thermal conductivity hydrophobic core microcapsules; Preparation of cement based on double-shell low thermal conductivity hydrophobic capsule core microcapsules: (9) Add 78.4% of the dry material of the corrosion-resistant cementitious material into the cement paste mixer container and stir at a low speed of 100 r / min for 2 minutes to ensure that the dry material is fully mixed, wherein the dry material of the corrosion-resistant cementitious material includes slag: fly ash in a mass ratio of 4:1; (10) Weighing liquid sodium silicate and NaOH to prepare an alkali-activated solution, cooling the alkali-activated solution to room temperature, and then pouring the alkali-activated solution into the corrosion-resistant cementitious material dry material stirred uniformly in step (9) in an amount of 30 wt % of the corrosion-resistant cementitious material dry material, and adding water in a ratio of 0.4 of the corrosion-resistant cementitious material dry material, and continuing to stir at a low speed of 100 r / min for 2 min, and then standing for 120 s and stirring at a high speed of 200 r / min for 2 min to form a corrosion-resistant mixed slurry; (11) 11.76% of thermal insulation admixture silica aerogel, 7.84% of double-shell microcapsules, and 2% of organic inert anticorrosive emulsion styrene-butadiene latex are added to the geopolymer slurry in step (10) in proportion, and the mixture is stirred at a low speed of 100 r / min for 5 min to form a cement slurry based on double-shell hydrophobic core microcapsules.

[0036] The prepared low thermal conductivity hydrophobic capsule core microcapsules were subjected to SEM scanning, and the scanning results are as follows Figure 4 As shown, Figure 4 (a) is the SEM scan of a single-layer unmodified microcapsule, and (b) is the SEM scan of a double-shell microcapsule. Figure 4 (c) is the enlarged SEM scan of the inorganic capsule shell. Figure 4 (d) is an enlarged SEM scan of the organic capsule shell. Figure 5 This is a TEM image of a double-shell microcapsule. It can be seen from the figure that the capsule core is wrapped and adsorbed in the aerogel capsule shell with a porous structure inside; Figure 6 This is the energy spectrum of the double-shell microcapsule. According to the quantitative element test results of the spectrum, the mass proportion of the C element is 42.67% and the mass proportion of the O element is 23.53%, indicating that PVA effectively covers the capsule shell. Figure 7 is the element distribution diagram of the modified double-shell microcapsules, where Figure 7 (a) is the TEM morphology of the microcapsule. Figure 7 (b) is the distribution diagram of Si element. Figure 7 (c) is the distribution diagram of O element. Figure 7 (d) is the distribution diagram of C element, Figure 7 It can be seen that C and O elements are evenly distributed within the microcapsules, indicating that the PVA film effectively covers the single-layer aerogel microcapsules.

[0037] Embodiment 2: Provide a method for preparing cement, comprising the following steps: Preparation of low thermal conductivity hydrophobic capsule core microcapsules, the preparation process is referred to the attached Figure 2 As shown: (1) After passing the hydrophobic SiO2 aerogel through a 50-mesh sieve, it was placed in a drying oven and dried at a constant temperature of 105°C for 8 hours; (2) preheating the capsule core material polymethylhydrogensiloxane at 60°C for 2 hours; (3) Using a powerful stirrer, set the speed of polymethyl hydrogen siloxane to 1000 r / min, stir for 5 minutes, pour in the hydrophobic SiO2 aerogel, mix well, adjust the stirring speed to 500 r / min, and continue stirring for 3 minutes, wherein the mass ratio of polymethyl hydrogen siloxane to hydrophobic SiO2 aerogel is 80:100; (4) After filtering the mixed material, cooling it to room temperature and drying it for 24 hours, a single-shell microcapsule with a hydrophobic surface and low thermal conductivity was obtained; Hydrophilic modification of low thermal conductivity hydrophobic core microcapsules and organic shell encapsulation: (5) Mixing silane coupling agent γ-aminopropyltriethoxysilane and water in a ratio of 25:75, placing the mixture on a 60°C constant temperature magnetic stirrer, stirring at a speed of 1000 r / min for 5 min, and cooling the mixture to room temperature to prepare a silane coupling agent hydrolyzed solution; (6) Spray the hydrolyzed solution of silane coupling agent onto the surface of the microcapsules, stirring continuously during the spraying process to ensure uniformity; (7) The microcapsules sprayed with the hydrolyzed silane coupling agent solution in step (6) are statically sealed for 24 hours, and then heated at a constant temperature of 120° C. for 15 minutes to obtain inorganic single-shell low thermal conductivity microcapsules with a hydrophilic exterior and a hydrophobic core; (8) preparing a 1% polyvinyl alcohol solution, spraying the surface of SiO2 aerogel single-layer shell hydrophobic core microcapsules with the solution, and then drying at a constant temperature of 60°C for 12 hours to form organic / inorganic double-shell low thermal conductivity hydrophobic core microcapsules; Preparation of cement based on double-shell low thermal conductivity hydrophobic capsule core microcapsules: (9) Add 76.8% of the dry material of the corrosion-resistant cementitious material into the cement paste mixer container and stir at a low speed of 100 r / min for 2 minutes to ensure that the dry material is fully mixed, wherein the dry material of the corrosion-resistant cementitious material includes slag: fly ash in a mass ratio of 4:1; (10) Weigh liquid sodium silicate and NaOH to prepare an alkali-activated solution. After cooling the alkali-activated solution to room temperature, pour the alkali-activated solution into the corrosion-resistant cementitious material dry material stirred uniformly in step (9) in an amount of 30 wt % of the corrosion-resistant cementitious material dry material, and add water in a ratio of 0.4 of the corrosion-resistant cementitious material dry material. Continue stirring at a low speed of 100 r / min for 2 min, let it stand for 120 s, and then stir at a high speed of 200 r / min for 2 min to form a corrosion-resistant mixed slurry; (11) 13.44% of hollow glass microspheres as a thermal insulation admixture, 5.76% of double-shell microcapsules, and 4% of an organic inert anticorrosive emulsion epoxy resin were added to the geopolymer slurry in step (10) in proportion, and the mixture was stirred at a low speed of 100 r / min for 5 min to form a cement slurry based on double-shell hydrophobic core microcapsules.

[0038] Embodiment 3: Provide a method for preparing cement, comprising the following steps: Preparation of low thermal conductivity hydrophobic capsule core microcapsules, the preparation process is referred to the attached Figure 2 As shown: (1) After passing the hydrophobic SiO2 aerogel through a 50-mesh sieve, it was placed in a drying oven and dried at a constant temperature of 105°C for 8 hours; (2) preheating the capsule core material n-isoalkane at 60 °C for 2 h; (3) Using a powerful stirrer, set the speed of n-isomerized alkane to 1000 r / min, stir for 5 min, then pour into the hydrophobic SiO2 aerogel. After mixing evenly, adjust the stirring speed to 500 r / min and continue stirring for 3 min. The mass ratio of n-isomerized alkane to hydrophobic SiO2 aerogel is 80:100. (4) After filtering the mixed material, cooling it to room temperature and drying it for 24 hours, a single-shell microcapsule with a hydrophobic surface and low thermal conductivity was obtained; Hydrophilic modification of low thermal conductivity hydrophobic core microcapsules and organic shell encapsulation: (5) Mixing γ-aminopropyltriethoxysilane and water in a ratio of 30:70, placing the mixture on a 60°C constant temperature magnetic stirrer, stirring at a speed of 1000 r / min for 5 min, and cooling the mixture to room temperature to prepare a silane coupling agent hydrolyzed solution; (6) Spray the hydrolyzed solution of silane coupling agent onto the surface of the microcapsules, stirring continuously during the spraying process to ensure uniformity; (7) The microcapsules sprayed with the hydrolyzed silane coupling agent solution in step (6) are statically sealed for 24 hours, and then heated at a constant temperature of 120° C. for 15 minutes to obtain inorganic single-shell low thermal conductivity microcapsules with a hydrophilic exterior and a hydrophobic core; (8) preparing a 2% polyvinyl alcohol solution, spraying the surface of SiO2 aerogel single-layer shell hydrophobic core microcapsules with the solution, and then drying at a constant temperature of 60°C for 12 hours to form organic / inorganic double-shell low thermal conductivity hydrophobic core microcapsules; Preparation of cement based on double-shell low thermal conductivity hydrophobic capsule core microcapsules: (9) Add 75.2% of the dry materials of the corrosion-resistant cementitious material into the cement slurry mixer container and stir at a low speed of 100 r / min for 2 min to ensure that the dry materials are fully mixed, wherein the dry materials of the corrosion-resistant cementitious material include slag: fly ash in a mass ratio of 4:1; (10) Weighing liquid sodium silicate and NaOH to prepare an alkali-activated solution, cooling the alkali-activated solution to room temperature, pouring the alkali-activated solution into the corrosion-resistant cementitious material dry material stirred uniformly in step (9) in an amount of 30 wt % of the corrosion-resistant cementitious material dry material, and adding water in a ratio of 0.45 of the corrosion-resistant cementitious material dry material, continuing to stir at a low speed of 100 r / min for 2 min, and then stirring at a high speed of 200 r / min for 2 min after standing for 120 s to form a corrosion-resistant mixed slurry; (11) 15.04% of thermal insulation admixture fly ash beads, 3.76% of double-shell microcapsules, and 6% of organic inert anticorrosive emulsion styrene-butadiene latex were added to the geopolymer slurry in step (10) in proportion, and the mixture was stirred at a low speed of 100 r / min for 5 min to form a cement slurry based on double-shell hydrophobic core microcapsules.

[0039] Example 4: A method for preparing cement is provided. Compared with Example 3, the difference is that the mass fractions of corrosion-resistant cementitious material, thermal insulation admixture, double-shell microcapsule and styrene-butadiene latex are 68.6%, 21.56%, 7.84% and 2%, respectively, and the remaining steps are the same.

[0040] Example 5: A method for preparing cement is provided. Compared with Example 3, the difference is that the mass fractions of corrosion-resistant cementitious material, thermal insulation admixture, double-shell microcapsule and styrene-butadiene latex are 67.2%, 23.04%, 5.76% and 4%, respectively, water is added at a ratio of 0.5 of the dry material of corrosion-resistant cementitious material, and the other steps are the same.

[0041] Example 6: A method for preparing cement is provided. Compared with Example 5, the difference is that the mass fractions of corrosion-resistant cementitious material, thermal insulation admixture, double-shell microcapsule and styrene-butadiene latex are 65.8%, 24.44%, 3.76% and 6%, respectively, and the remaining steps are the same.

[0042] Comparative Example 1: A method for preparing cement is provided, comprising the following steps: Grade G oil well cement was put into the cement slurry mixer container and stirred at a low speed of 100 r / min for 2 min. Water was added according to the cement ratio of 0.44, and the mixture was stirred at a low speed of 100 r / min for 2 min. After standing for 120 s, the mixture was stirred at a high speed of 200 r / min for 2 min to form the slurry of comparative example 1.

[0043] Comparative Example 2: A method for preparing cement is provided, comprising the following steps: (1) Add the dry material of corrosion-resistant cementitious material into the cement slurry mixer container and stir at a low speed of 100 r / min for 2 minutes to ensure that the dry material is fully mixed; (2) Weigh liquid sodium silicate and NaOH to prepare an alkali-activated solution. After cooling the alkali-activated solution to room temperature, pour the alkali-activated solution into the uniformly stirred dry corrosion-resistant cementitious material in step (1) in an amount of 30 wt % of the dry corrosion-resistant cementitious material, and add water in a ratio of 0.4 of the dry corrosion-resistant cementitious material. Continue stirring at a low speed of 100 r / min for 2 min, let it stand for 120 s, and then stir at a high speed of 200 r / min for 2 min to form a mixed slurry of comparative example 2.

[0044] Comparative Example 3: A method for preparing cement is provided, comprising the following steps: (1) Add 88.24% of the dry material of corrosion-resistant cementitious material into the cement slurry mixer container and stir at a low speed of 100 r / min for 2 minutes to ensure that the dry material is fully mixed; (2) Weigh liquid sodium silicate and NaOH to prepare an alkali-activated solution. After cooling the alkali-activated solution to room temperature, pour it into the dry material of the corrosion-resistant cementitious material in an amount of 30 wt% of the dry material of the corrosion-resistant cementitious material, and add water in a ratio of 0.4 of the dry material of the corrosion-resistant cementitious material. Continue to stir at a low speed of 100 r / min for 2 min, let it stand for 120 s, and then stir at a high speed of 200 r / min for 2 min to obtain a corrosion-resistant cementitious slurry; (3) Add 11.76% by mass of a thermal insulation admixture to the corrosion-resistant gelled slurry in step (2), and continue stirring at a low speed of 100 r / min for 5 minutes to form Comparative Example 3.

[0045] Comparative Example 4: A method for preparing cement is provided, comprising the following steps: (1) Add 86.24% of the mass fraction of corrosion-resistant cementitious material into the cement slurry mixer container and stir at a low speed of 100 r / min for 2 min to ensure that the dry material is fully mixed; (2) Weigh liquid sodium silicate and NaOH to prepare an alkali-activated solution. After cooling the alkali-activated solution to room temperature, pour it into the dry material of the corrosion-resistant cementitious material in an amount of 30 wt% of the dry material of the corrosion-resistant cementitious material, and add water in a ratio of 0.4 of the dry material of the corrosion-resistant cementitious material. Continue to stir at a low speed of 100 r / min for 2 min, then let it stand for 120 s and stir at a high speed of 200 r / min for 2 min to obtain a corrosion-resistant cementitious slurry; (3) Add 11.76% by mass of thermal insulation admixture aerogel and 2% by mass of styrene-butadiene latex into the corrosion-resistant gelled slurry in step (2), and continue stirring at a low speed of 100 r / min for 5 min to form Comparative Example 4.

[0046] Example 7: A method for preparing cement is provided. Compared with Example 1, the difference is that the mass fractions of corrosion-resistant cementitious material, thermal insulation admixture, double-shell microcapsule and styrene-butadiene latex are 65.0%, 21.56%, 8% and 5.44% respectively, and the remaining steps are the same.

[0047] Example 8: A method for preparing cement is provided. Compared with Example 1, the difference is that the mass fractions of corrosion-resistant cementitious material, thermal insulation admixture, double-shell microcapsule and styrene-butadiene latex are 79.16%, 11.76%, 3.5% and 5.58%, respectively, and the remaining steps are the same.

[0048] Example 9: A method for preparing cement is provided. Compared with Example 1, the difference is that the mass fractions of corrosion-resistant cementitious material, thermal insulation admixture, double-shell microcapsule and styrene-butadiene latex are 73.09%, 15.76%, 4.15% and 7%, respectively, and the remaining steps are the same.

[0049] Example 10: A method for preparing cement is provided. Compared with Example 1, the difference is that the mass fractions of corrosion-resistant cementitious material, thermal insulation admixture, double-shell microcapsule and styrene-butadiene latex are 66.85%, 25.15%, 4.75% and 3.25%, respectively, and the remaining steps are the same.

[0050] Example 11: A method for preparing cement is provided. Compared with Example 1, the difference is that the mass ratio of dimethyl silicone oil to hydrophobic SiO2 aerogel is 68:100, and the other steps are the same.

[0051] Example 12: A method for preparing cement is provided. Compared with Example 1, the difference is that the concentration of the polyvinyl alcohol solution is 4%, and the other steps are the same.

[0052] Example 13: A method for preparing cement is provided. Compared with Example 1, the difference is that the concentration of the polyvinyl alcohol solution is 0.8%, and the other steps are the same.

[0053] Comparative Example 5: A method for preparing cement is provided. Compared with Example 1, the difference is that step (5), step (6), step (7) and step (8) are removed, and the surface hydrophobic single-shell low thermal conductivity microcapsules obtained in step 4 are directly subjected to step (9), and the remaining steps are the same.

[0054] Example 14: A method for preparing cement is provided. Compared with Example 1, the difference is that step (5), step (6) and step (7) are removed, and the remaining steps remain unchanged.

[0055] For ease of understanding, the raw material formulas of the cement slurries of Examples 1-10 and Comparative Examples 2-4 are compared, and the results are shown in Table 1 below: Table 1 Material Project Corrosion resistant cementitious material% Thermal insulation admixture% latex% Microcapsule% Water-cement ratio Example 1 78.4 11.76 2 7.84 0.4 Example 2 76.8 13.44 4 5.76 0.4 Example 3 75.2 15.04 6 3.76 0.45 Example 4 68.6 21.56 2 7.84 0.45 Example 5 67.2 23.04 4 5.76 0.5 Example 6 65.8 24.44 6 3.76 0.5 Example 7 65.0 21.56 5.44 8 0.4 Example 8 79.16 11.76 5.58 3.5 0.4 Example 9 73.09 15.76 7 4.15 0.4 Example 10 66.85 25.15 3.25 4.75 0.4 Comparative Example 2 100 / / / 0.4 Comparative Example 3 88.24 11.76 / / 0.4 Comparative Example 4 86.24 11.76 2 / 0.4 After the cement slurries prepared in Examples 1 to 14 and Comparative Examples 1 to 5 were cured at room temperature for 1 day + 90°C to form cement stone specimens, the uniaxial compressive strength and thermal conductivity before corrosion were measured, wherein the temperature point for the thermal conductivity test was selected as 90°C. The corrosion conditions of the specimens were 100°C, CO2 partial pressure 5MPa, Na2SO4 concentration 5% ion solution, and the corrosion time was 7 days. Observation and testing were performed, and the results are as follows: Comparative Example 1 is oil well cement with a water-cement ratio of 0.44. After 1d of normal temperature + 3d of high temperature curing at 90℃, the thermal conductivity is 0.9503W / (m•K), and the decrease rate of compressive strength after corrosion is 24.01%; Comparative Example 2 is a geopolymer cementitious material without any admixture, with a water-cement ratio of 0.4. The thermal conductivity of the cement paste after curing at room temperature for 1d + 90℃ for 3d is 0.6787W / (m•K), and the decrease rate of its compressive strength after corrosion is 15.26%, indicating that the corrosion resistance and thermal insulation properties of the corrosion-resistant cementitious material itself are improved compared with oil well cement. The raw materials of Comparative Example 3 include 88.24% of corrosion-resistant gelling material and 11.76% of thermal insulation material. Compared with Comparative Example 2, due to the loose porous structure of the thermal insulation additive, the thermal conductivity of the material decreased by 0.2310W / (m•K), but its strength decay rate after corrosion increased to 18.34%. This shows that although the addition of thermal insulation material is conducive to the reduction of thermal conductivity, it has an adverse effect on the corrosion resistance of the material; Comparative Example 4 includes 86.24% of corrosion-resistant gelling material, 11.76% of thermal insulation material and 2% latex, and its thermal conductivity is 0.4505W / (m•K), and the compressive strength reduction rate after corrosion is 13.73%. Compared with Comparative Example 3, after adding 2% latex in Comparative Example 4, its thermal conductivity does not change much, but the compressive strength attenuation rate after corrosion is reduced, which shows that latex has a certain effect on improving the corrosion resistance of the material. The difference between Comparative Example 4 and Example 1 is that 7.84% of the microcapsules in the composition of Example 1 are replaced by corrosion-resistant gelling material. Compared with Comparative Example 4, the thermal conductivity of Example 1 is reduced by 0.0988W / (m•K), a reduction of 21.93%, and its strength attenuation rate after corrosion is reduced from 13.73% to 2.39%. It shows that the double-shell hydrophobic capsule core microcapsule has excellent effects in reducing thermal conductivity and improving the corrosion resistance of materials.

[0056] Attached Figure 8 The figure shows the surface morphology of the specimens of Example 1 before corrosion (a) and after corrosion (b), and of Comparative Example 1 before corrosion (c) and after corrosion (d). The corrosion conditions are 100°C, CO2 partial pressure 5MPa, Na2SO4 concentration 5% ion solution, and the corrosion time is 7 days. The figure shows that after H2CO3, SO4 2- After corrosion, the color of the sample of Example 1 changed from dark green before corrosion to gray, and no peeling phenomenon occurred on the surface. However, the surface of Comparative Example 1 turned black after corrosion, and obvious peeling occurred on the surface, indicating that the degree of carbonization of Comparative Example 1 was higher.

[0057] Attached Fig. 9 With attached Fig.10The results of thermal conductivity and compressive strength decay rate of Example 1, Example 2 and Example 3 show that the thermal conductivity of the material decreases with the increase of the content of thermal insulation admixture, but its strength decay rate after corrosion gradually increases. This shows that the porous structure of the thermal insulation admixture is conducive to the reduction of thermal conductivity, but is not conducive to the corrosion resistance of the material. Although the latex content increases synchronously with the increase of the thermal insulation admixture content in Example 1, Example 2 and Example 3, the reduction in the amount of double-shell hydrophobic capsule core microcapsules leads to an increase in the strength decay rate after corrosion, indicating that for geothermal insulation cement rich in porous structure, the effect of latex on improving the material's anti-corrosion performance is not as good as that of double-shell hydrophobic capsule core microcapsules. Comparing Example 1 with Example 4, the amount of latex added in the composition is 2% and the amount of microcapsule added is 7.84% unchanged, but the amount of thermal insulation admixture is increased by 9.8%, resulting in a decrease in the thermal conductivity of the material by 0.0746W / (m•K) and an increase in the strength attenuation rate by 0.83%. That is, when the content of microcapsules is high, the increase of thermal insulation admixture will not cause a significant increase in the strength attenuation rate. Compared with Example 1, in Example 2 with a lower content of microcapsules, the increase of thermal insulation admixture will cause a significant increase in the strength attenuation rate. In Example 2 and Example 5, the amount of latex added was 4% and the amount of microcapsules added was 5.76% unchanged, and the amount of thermal insulation admixture increased by 9.6%, causing the thermal conductivity of the material to decrease by 0.0667W / (m•K) and the strength attenuation rate to increase by 1.76%; in comparison with Example 3 and Example 6, the amount of latex added was 6% and the amount of microcapsules added was 3.76% unchanged, and the amount of thermal insulation admixture increased by 9.4%, causing the thermal conductivity of the material to decrease by 0.0781W / (m•K) and the strength attenuation rate to increase by 2.15%. This shows that when the aerogel content increases and the amount of latex and microcapsules added remains unchanged, the higher amount of microcapsules added by 7.84% is more conducive to maintaining the corrosion resistance of the material than the higher amount of latex added by 6%.

[0058] Attached Fig.11 With attached Fig.12 The thermal conductivity and compressive strength attenuation rate comparison diagrams of Example 1, Examples 7-14 and Comparative Example 5 are respectively shown.

[0059] The figure shows that compared with Example 1, the thermal conductivity of Example 7 is 0.4024W / (m•K) and the compressive strength attenuation rate is increased to 7.95%. The reason for the increase in thermal conductivity and compressive strength attenuation rate is that the content of corrosion-resistant cementitious material is too low and the content of microcapsules is increased, which is not conducive to the bonding and wrapping of microcapsules by the cement matrix, so the overall structure of the cement is loose. Too little cementitious material is easy to form through cracks in the cement matrix, causing the thermal conductivity to increase, and the number of channels for ion solution to erode the cement matrix is ​​increased, which is not conducive to the corrosion resistance of the material.

[0060] Compared with Example 1, the thermal conductivity of Example 8 is 0.3835W / (m•K), and the thermal conductivity is increased, indicating that the content of microcapsules cannot be too low. At the same time, relative to Example 1, its compressive strength attenuation rate is increased to 6.41%, because the content of microcapsules is reduced to 3.5%. Although the corrosion-resistant cementitious material has increased to 79.16%, the corrosion resistance mechanism of the alkali-activated cementitious material is that its own hydration product is low alkalinity, and its corrosion resistance is not as good as that of the silicone that relies on the formation of a hydrophobic film. Therefore, when the content of microcapsules is set to be higher than 3.76% and the content of corrosion-resistant cementitious material is set to be lower than 78.4%, the overall performance of the cement structure is better.

[0061] Compared with Example 1, the thermal conductivity of Example 9 is 0.4371 W / (m•K), and the compressive strength attenuation rate is increased to 9.46%. The thermal conductivity and compressive strength attenuation rate are both increased. The reason is that the increase in latex content leads to an increase in the liquid phase content in the cement slurry, and a decrease in the content of alkali-activated solution required for the cementitious material, resulting in insufficient cement setting time and hydration reaction, weakening of the overall structure of the cement stone, and a large increase in the thermal conductivity and compressive strength attenuation rate of the material.

[0062] Compared with Example 1, the thermal conductivity of Example 10 is 0.3926 W / (m•K), and its compressive strength attenuation rate is increased to 8.83%. The reason is that the volume content of the porous insulation material with lower density is too high, and the wrapping and bonding effect of the cementitious material on the insulation material and the microcapsules is poor, causing the material structure strength to decrease and the corrosion resistance to be significantly reduced, resulting in a higher compressive strength attenuation rate. Therefore, when the content of the thermal insulation admixture is set to less than 24.44%, the performance of the cement structure is better.

[0063] Compared with Example 1, the difference of Example 11 is that the mass ratio of dimethyl silicone oil to hydrophobic SiO2 aerogel is 68:100, the proportion of its hydrophobic capsule core is reduced, and the thermal conductivity of the microcapsule itself is slightly reduced, so the thermal conductivity of Example 11 is slightly reduced to 0.3385W / (m•K). The compressive strength attenuation rate is increased to 7.50%, because the capsule core is the main agent for forming the system corrosion protection, and the content of the hydrophobic capsule core is crucial to the anti-corrosion performance of cement stone. The reduction of the capsule core content is not conducive to the corrosion resistance of cement.

[0064] Compared with Example 1, Example 12 is different in that the concentration of the polyvinyl alcohol solution is 4%, but due to the excessive viscosity of the polyvinyl alcohol solution at this concentration, the coating and wrapping effect of the outer organic capsule shell is poor, the strength of the microcapsules themselves is reduced, and some inorganic capsule shells are insufficiently covered. The microcapsules are easily broken prematurely during mechanical stirring, and the hydrophobic capsule core leaks, resulting in weakened cement stone structure, poor corrosion resistance of the material, and increased compressive strength attenuation rate. The thermal conductivity of this embodiment is 0.3806W / (m•K), and the compressive strength attenuation rate rises to 5.52%, so it is more appropriate when the concentration of the polyvinyl alcohol solution is less than or equal to 3.5%.

[0065] Compared with Example 1, Example 13 is different in that the concentration of the polyvinyl alcohol solution is 0.8%. However, due to the low concentration, the outer organic capsule shell wrapping effect is also poor. The strength of the microcapsules themselves decreases, and the microcapsules are easily broken and the hydrophobic capsule core leaks during mechanical stirring. The exposure of the single-layer capsule shell modified by the silane coupling agent affects the cement hydration process and weakens the cement stone structure, thus causing the corrosion resistance of the material to deteriorate, and the compressive strength attenuation rate to increase significantly. Its thermal conductivity is 0.3792W / (m•K), and the compressive strength attenuation rate increases to 8.49%.

[0066] In comparative example 5, the surface hydrophobic single capsule shell low thermal conductivity microcapsules were directly used to prepare corrosion-resistant geothermal cement materials. Due to the lack of surface modification and organic capsule shell coating, the surface hydrophobic single capsule shell low thermal conductivity microcapsules had poor compatibility with the corrosion-resistant cementitious materials, resulting in slurry delamination, the thermal conductivity of the cement stone increased to 0.4281W / (m•K), the overall structural strength decreased, the corrosion resistance weakened, and the compressive strength attenuation rate increased to 10.65%.

[0067] Example 14: The single-layer inorganic shell microcapsules that have not been hydrophilically modified are organically coated and used to prepare corrosion-resistant geothermal cement materials. However, since the inorganic hydrophobic shells have not been hydrophilically modified, the polyvinyl alcohol aqueous solution cannot effectively cover and coat the surface, and the microcapsules with complete organic shells cannot be formed, and the compatibility with cement deteriorates. Therefore, the thermal conductivity coefficient increases to 0.3750 W / (m•K), the strength of the microcapsules themselves decreases, and the compatibility with cement weakens, resulting in the weakening of the overall structure of the cement stone. The attenuation rate of the compressive strength of the cement stone after corrosion increases to 8.17%.

[0068] In general, the embodiments of the present invention prepare geothermal thermal insulation and anti-corrosion cement based on the preparation of double-shell low thermal conductivity hydrophobic capsule core microcapsules. The hydrophobic liquid capsule core continuously released by the double-shell hydrophobic capsule core microcapsules is used to prevent the migration of acidic ion solutions inside the cement stone material to avoid corrosion of the cement matrix. Polyvinyl alcohol and aerogel are used to encapsulate the hydrophobic capsule core. Through the formation of the hydrophobic properties of the cement ring, water-carrying ions are prevented from invading the cement matrix, thereby improving the corrosion resistance of the thermal insulation cement ring in the corrosive environment of multi-ion solutions rich in acidic media. This method can be used not only in geothermal thermal insulation cementing cement, but also in conventional geothermal cementing cement or acidic oil and gas reservoir cementing.

[0069] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A double-shell microcapsule, characterized in that: It comprises a capsule core, an inorganic capsule shell and an organic capsule shell, wherein the capsule core is coated inside the inorganic capsule shell, and the organic capsule shell is coated outside the inorganic capsule shell; The inorganic capsule shell comprises a porous structure, the capsule core comprises a hydrophobic substance, and the organic capsule shell is configured to mechanically protect the inorganic capsule shell; The inorganic capsule shell can react with the formation medium, and the organic capsule shell can be dissolved in the formation medium.

2. A double-shell microcapsule according to claim 1, characterized in that: The capsule core comprises at least one of dimethyl silicone oil, polymethyl hydrogen siloxane and normal isoparaffin, the inorganic capsule shell comprises SiO2 aerogel material, and the organic capsule shell comprises polyvinyl alcohol.

3. A double-shell microcapsule according to claim 2, characterized in that: The mass ratio of the capsule core to the inorganic capsule shell is 70-85:100, the thermal conductivity of the capsule core is 0.07-0.20 W / (m•K), and the thermal conductivity of the inorganic capsule shell is 0.015-0.020 W / (m•K).

4. A method for preparing double-shell microcapsules, characterized in that: The following steps are involved: S1: mixing the capsule core and the inorganic capsule shell and drying them to obtain a single-layer microcapsule; S2: hydrophilic modification of the single-layer microcapsules; S3: encapsulating the organic capsule shell to obtain double-shell microcapsules.

5. The method for preparing a double-shell microcapsule according to claim 4, characterized in that: The hydrophilic modification process in S2 includes spraying a silane coupling agent hydrolyzed solution on the surface of the single-layer microcapsule, wherein the mass fraction of the silane coupling agent hydrolyzed solution is 25-30%.

6. The method for preparing a double-shell microcapsule according to claim 4, characterized in that: The encapsulation of the organic capsule shell in S3 comprises re-coating the modified single-layer microcapsule with a polyvinyl alcohol aqueous solution; The mass fraction of the polyvinyl alcohol aqueous solution is 1-3%.

7. A cement, characterized in that: It comprises corrosion-resistant gelling material, thermal insulation admixture, organic inert antiseptic emulsion and double-shell microcapsule according to any one of claims 1 to 3, and the weight percentages are 65.8% to 78.4%, 11.76% to 24.44%, 2% to 6% and 3.76% to 7.84% respectively.

8. A cement according to claim 7, characterized in that: The corrosion-resistant cementitious material comprises slag and fly ash, and the weight ratio of slag to fly ash is 3.5-4.5:1; The organic inert antiseptic emulsion includes styrene-butadiene latex or epoxy resin; The thermal insulation admixture includes at least one of vitrified microspheres, fly ash floating beads, hollow glass microspheres, and silica aerogel.

9. A method for preparing cement, characterized in that: The following steps are involved: Mixing the alkali-activated solution with the corrosion-resistant gelling material to obtain a corrosion-resistant mixed slurry; Add a thermal insulation admixture, an organic inert anticorrosive emulsion and double-shell microcapsules prepared by the preparation method according to any one of claims 4 to 6 into the corrosion-resistant mixed slurry, stir and mix them to obtain cement slurry.

10. The method for preparing cement according to claim 9, characterized in that: The alkaline excitation solution includes sodium silicate and NaOH. In the configuration of the alkaline excitation solution, NaOH is weighed according to the following formula: m(NaOH)=27.78 / x-10.7, where m is the mass of NaOH, x is the modulus of sodium silicate, and x= 1.3~1.5.

Citation Information

Patent Citations

  • Composite structure self-repairing microcapsule particle as well as preparation method and application thereof

    CN110776270A

  • Super-hydrophobic microcapsule polymer cement-based anticorrosive coating as well as preparation method and application thereof

    CN111875320A

  • Thermal insulation cement material for upper well section of geothermal well and preparation method of thermal insulation cement material

    CN116986852A

Cited By

  • Condensation-resistant heat-preservation type super-hydrophobic aerogel coating, preparation method thereof and application of aerogel coating in industrial thermal equipment

    CN122587590A